Jurnal Implementasi Cloud Computing Berbasis Open Source Dengan Metode Private Cloud Storage Pada SMP Negeri 1 Rantau Selatan - Pahri aulia Sarumpaet (LPPM Universitas Al Washliyah Labuhanbatu, 2024)
SMP N 1 Rantau Selatan is a junior high school located in Sioldengan Village, Rantau Selatan District, Labuhanbatu Regency, North Sumatra. As time went on, junior high schools experienced many problems in managing centralized data storage media, synchronizing between devices and file sharing. Where data storage is carried out on each computer not centralized and file sharing is still manual between one computer and another. Making it difficult for teachers and students of SMP Negeri 1 Rantau Selatan to do file sharing and centralized data storage. So through the authors of SMP Negeri 1 Rantau Selatan, they have an innovation to implement the Cloud Computing system to overcome this problem. Cloud Computing is a client-server model, where resources such as servers, storage, network and software can be viewed as services that can be accessed by users remotely and at any time. Cloud computing infrastructure such as: servers, storage, network, and various software is called